Identifcation of Useful Chemical Content of Red and White Jabon Leaf (Anthocephalus spp.) - Martini Wali; Noor Farikhah Haneda; Nina Maryana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
Jabon (Anthocephalus spp.) is a tree that has multiple functions. In addition to timber, jabon also useful as medicinalplants and fodder. This study aims to determine the primary compound content and the content of secondary metaboliccompounds in the leaves of red and white jabon. Test methods used were the proximate test for identification of primarycompounds and phytochemicals testing for the identification of secondary metabolic compounds from the jabon leaves. Ingeneral, the proximate test results show that white jabon leaves contain moisture, crude protein, crude fiber, ADF (AcidDetergent Fiber) and lignin in a greater percentage than that of red jabon 96.35%, 16.44%, 14.49%, 38.72%, 24.21%,respectively. Red jabon leaves contain more crude fat and cellulose, i. e. 3.15% and 10.13 %, respectively, while othercomponent such as ash content, NFE (Nitrogen Free Extract), Ca, P, N and silica with values 6.72%, 56.29%, 1.47 %,0.25%, 2.63%, 0.04% on white jabon, and 6.95%, 56.16%, 1.84%, 0.32%, 2.36%, 0.07% on red jabon. The content ofsalt (NaCl) in the same percentage is 0.03%. The test results showed that the phytochemical compounds identified arequinone compounds and steroids with higher concentration on leaves of red jabon than white jabon leaves. Based on thecolor type of quinone compounds were identified class of anthraquinone compounds. The results showed that the leavesof red jabon can be used as medicinal plants because they contain substantial amount of secondary metaboliccompounds. White jabon can be used as an alternative feed source for livestock because it contains more nutritioncompounds.